Stream fish assemblages in the Eastern Amazon: the role of small tetras (Characidae) in alpha diversity and taxonomic structure - Casatti, Lilian [UNESP]; Brejão, Gabriel Lourenço [UNESP]; Carvalho, Fernando Rogério; da Costa, Victoria Santos [UNESP]; da Cruz, Gabriel Martins; Dias-Silva, Karina; Langeani, Francisco [UNESP]; de Lucena, Maria Dayanne Lima; Oliveira-Junior, José Max Barbosa; Michelan, Thaisa Sala; Montag, Luciano Fogaça de Assis; Oliveira, Beatriz da Cruz [UNESP]; et al. (FapUNIFESP (SciELO), 2024)
Wallacean shortfalls in knowledge about biodiversity, especially in the Amazon biome, can only be addressed by increasing sampling efforts in focal areas. The objective of this study was to describe the fish fauna of streams associated with four protected areas in the Eastern Amazon. These areas include the Tapajós (Parque Nacional da Amazônia, Parque Nacional do Jamanxim) and Trombetas drainages (Floresta Nacional Saracá-Taquera), and Tapajós/Xingu interfluve (Reserva Biológica Nascentes da Serra do Cachimbo), state of Pará, Brazil. In the 99 stream reaches surveyed, 176 fish species were recorded. Almost a third of the species and specimens belong to the Characidae family, predominantly represented by small tetras (known as piabas or lambaris). One threatened species (Harttia dissidens) was registered. Of the total richness, 24 species were singletons and associated with specific habitats. The highest taxonomic distinctness was observed for Floresta Nacional Saracá-Taquera, while streams within the Parque Nacional da Amazônia exhibited the greatest taxonomic distinctness variation. Compared to existing records in scientific collections covering stream fish fauna in watersheds of up to 4,300 hectares in Pará, our study added the record of eight other genera and identified relevant areas for additional surveys.
Keywords: Conservation units; Diversity; Protected areas; Rare species; Taxonomic distinctness